The Right to Liberty of Persons with Disabilities From the Statute of Persons with Disabilities - Panteleão Puccini Caminha, Anelize (Revue internationale des Gouvernements Ouverts, 2019)
[extract] From the most remote Western civilizations, the disabled person has always been marginalized in society under the stigma of inferiority. This reality, however, has been suffering from the impacts of a worldwide trend towards the promotion of its social inclusion, especially in the last decades. This work aims to analyze this social phenomenon, with an emphasis on the right of freedom of the disabled, in their legal-normative perspective. Given the repercussion of recent legislative innovations in numerous spheres of action of the individual, this theme is relevant and requires more in-depth reflection from the operators of the Law. In addition, statistical data reveal that this social segment corresponds to a significant percentage of the Brazilian population - 23.9% (twenty-three point nine percent) have some type of physical disability and 8.3% (eight point three percent) presents a severe deficiency - which claims the state and society at large - which seeks to be guided by the supreme values of freedom, security, well-being, development, equality and justice in a context of fraternity, pluralism and absence of prejudice - special attention. After delimiting the concept of handicapped, we will make a brief historical retrospect of the social insertion of the disabled person, from antiquity to the present. Next, we will approach the notions of autonomy and human dignity as guidelines of the legal rule and, subsequently, the freedom of the disabled, in light of Brazilian legislation, specifically Law 13,146, of July 6, 2015 Deficiency. The available jurisprudential collection is very small, thus the research will be supported predominantly by a bibliographical and normative one, by reading scientific works and articles published in national and international journals, that directly or indirectly face the proposed issues. Without intending to exhaust the subject, we will discuss the right of liberty of the disabled person from an eminently normative perspective, with the aim of contributing to the debate on the scope of the legislation of regency.